Motivation and Anxiety in Arabic Language Learning: Implications for Innovative Instruction - Putri Utami Fajriyanti; Daviq Habibulloh; Rizki Arif Wicaksono; Ikhtiar Andriyanto (Yayasan Lembaga Studi Makwa, 2026)
Motivation and anxiety are two psychological factors that strongly influence success in Arabic language learning. Motivation functions as an internal drive that encourages learners to study, practice, and achieve instructional goals, whereas anxiety may become a barrier that reduces confidence, participation, and communicative performance in Arabic. This study aims to describe the relationship between motivation and anxiety in Arabic language learning. The findings indicate that learners with higher motivation tend to show greater confidence and better control of anxiety during the learning process. In contrast, high levels of anxiety may reduce learning motivation and hinder academic achievement. These findings imply that Arabic language instruction should be supported by a learning environment that is encouraging, engaging, and responsive to learners’ psychological needs. Therefore, innovative instructional approaches are needed to strengthen motivation while reducing anxiety in order to improve the effectiveness of Arabic language learning. Abstrak Motivasi dan kecemasan merupakan dua faktor psikologis yang sangat memengaruhi keberhasilan pembelajaran bahasa Arab. Motivasi berperan sebagai dorongan internal yang menggerakkan peserta didik untuk belajar, berlatih, dan mencapai tujuan pembelajaran, sedangkan kecemasan dapat menjadi hambatan yang menurunkan kepercayaan diri, partisipasi, dan kemampuan berkomunikasi dalam bahasa Arab. Penelitian ini bertujuan untuk mendeskripsikan hubungan antara motivasi dan kecemasan dalam pembelajaran bahasa Arab. Hasil kajian menunjukkan bahwa peserta didik yang memiliki motivasi tinggi cenderung lebih percaya diri dan lebih mampu mengendalikan kecemasan selama proses belajar. Sebaliknya, tingkat kecemasan yang tinggi dapat menurunkan motivasi belajar dan menghambat pencapaian hasil belajar. Temuan ini menunjukkan bahwa pembelajaran bahasa Arab perlu didukung oleh lingkungan belajar yang suportif, menarik, dan responsif terhadap kebutuhan psikologis peserta didik. Oleh karena itu, diperlukan pendekatan pembelajaran yang inovatif untuk meningkatkan motivasi sekaligus mengurangi kecemasan guna mendukung pembelajaran bahasa Arab yang lebih efektif.